2013
DOI: 10.1186/1742-4690-10-122
|View full text |Cite
|
Sign up to set email alerts
|

S100A9 protein is a novel ligand for the CD85j receptor and its interaction is implicated in the control of HIV-1 replication by NK cells

Abstract: BackgroundThe reportedly broad expression of CD85j across different immune cell types suggests an importance for this molecule in the human immune system. Previous reports have shown that this receptor interacts with several HLA class-I molecules, as well as with some viral proteins. We have demonstrated that the subset of CD85j + Natural Killer (NK) cells efficiently controls human immunodeficiency virus type 1 (HIV-1) replication in monocyte-derived dendritic cells (MDDC) in vitro and this led us to hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 33 publications
3
45
0
Order By: Relevance
“…LILRB1 binds to β2m-associated HLA-I, whereas LILRB2 binds both β2m-associated and β2m-free heavy chain (FHC) forms of HLA-I [14]. Subsequent studies demonstrate LILRB binding to other ligands including the non-HLA angiopoietin-like (ANGPTL) protein family [15] and S100A8/S100A9 [16]. Structural analysis shows that two N-terminal Ig-like domains of LILRB1 and LILRB2 distinctly bind HLA as compared to the KIR–HLA interaction [17].…”
Section: Natural Ligands For Lilr Receptorsmentioning
confidence: 99%
“…LILRB1 binds to β2m-associated HLA-I, whereas LILRB2 binds both β2m-associated and β2m-free heavy chain (FHC) forms of HLA-I [14]. Subsequent studies demonstrate LILRB binding to other ligands including the non-HLA angiopoietin-like (ANGPTL) protein family [15] and S100A8/S100A9 [16]. Structural analysis shows that two N-terminal Ig-like domains of LILRB1 and LILRB2 distinctly bind HLA as compared to the KIR–HLA interaction [17].…”
Section: Natural Ligands For Lilr Receptorsmentioning
confidence: 99%
“…One recent study has implicated an interaction of LILRB1 with a damage-associated molecular pattern protein, S100A9. The interaction was found in a study to identify non-MHC-I ligands of LILRB1 on HIV-infected dendritic cells, because LILRB1 upregulation is associated with enhanced function in this context (58). The two other known receptors for S100A9 are TLR4 and receptor for advanced glycation end products (RAGE), and they are generally thought to promote inflammation.…”
Section: Host Immunomodulatory Proteinsmentioning
confidence: 99%
“…The findings of the interaction between LILRB1 and S100A9 await confirmation by other studies, as does better characterization of interaction. However, S100A9 can also function as a soluble tetramer, and stimulating LILRB1 + NK cells with exogenous tetrameric S100A9 marginally increases TNF-a production and produces some enhanced anti-HIV activity compared with unstimulated NK cells (58). The S100A9 protein can be held on the surface of an APC and could regulate other cells through LILRB1 in that context, too.…”
Section: Host Immunomodulatory Proteinsmentioning
confidence: 99%
“…LILRB5 was shown to bind to MHC-or human leukocyte antigen (HLA)-Class I heavy chains [44]. LILRB1 and 2 were also shown to bind to non-HLA ligands, including S100A8 and S100A9 for LILRB1 [51], and CD1d [52], several angiopoietin-like proteins (Angptls) [21,42], oligo-meric -amyloid [43], and myelin inhibitors reticulon 4 (RTN4, Nogo66), myelin associated glycoprotein (MAG), and oligodendrocyte myelin glycoprotein (OMgp) for LILRB2 [53]. We recently demonstrated that multimeric Angptls bind and activate LILRB2 more effectively than does HLA-G [42].…”
Section: Ligands For Itim-containing Receptorsmentioning
confidence: 99%
“…It also binds the cytomegalovirus UL18 protein, which is a HLA class I homolog [13]. In addition, LILRB1 was reported to bind two calcium-binding proteins S100A8 and S100A9 [51]. Dimerized HLA-G induces more efficient LILRB1 signaling than the monomeric form [61].…”
Section: Lilrb1 (Cd85j Ilt2 Lir1 Mir7)mentioning
confidence: 99%